The provision and effects of company training: A brief review of the literature - Rita Asplund (The Research Institute of the Finnish Economy (ETLA), 2004)
This non-technical paper attempts to explore our current state-of-knowledge on the economic benefits arising from company-provided training. More precisely, it reviews the empirical training literature in the search for answers to the following policy-relevant questions: What kind of training do companies provide? Who is trained, to what extent, and for which reasons? Do the trained employees experience an earnings advantage over the non-trained? Do training enhance employability, job mobility and promotion? Does the company benefit from its training investments in terms of improved productivity, competitiveness and profitability? Does the economy, and the society at large, benefit from companies' efforts to develop the skills of their labour? The review can be described as a scratch on the surface, with the emphasis being on some of the most recent empirical research on the training provided by companies and the economic implications of these activities for the employees, the company and the society. Despite a growing interest in investigating the incidence, determinants and impacts of companyprovided training, evidently inspired by better data and more sophisticated techniques, our current knowledge on the role and importance of the huge amounts of money that companies annually invest in the human capital of their employees is still quite limited, often involving contradictory findings. Consequently, great cautiousness is needed in drawing policy implications concerning the crucial questions of inequality of access to company training, on the one hand, and training market failures, on the other. – companies ; provision of training ; effect of training – – Tämän ei-teknisen katsauksen tavoitteena on hahmottaa tämän hetken tietämystämme yritysten tarjoaman koulutuksen taloudellisista hyödyistä. Alan empiirisestä kirjallisuudesta etsimme vastauksia seuraaviin koulutus- ja talouspoliittisesti keskeisiin kysymyksiin: Minkä tyyppistä koulutusta yritykset tarjoavat työntekijöilleen? Keitä yritys kouluttaa, missä määrin, ja mistä syistä? Hyötyvätkö työntekijät saamastaan koulutuksesta korkeamman palkan muodossa eikoulutettuihin kollegoihinsa verrattuna? Edistääkö työnantajien tarjoama koulutus yksilöiden työllistymistä, liikkuvuutta ja urakehitystä? Ovatko koulutusinvestoinnit hyödyllisiä yritysten tuottavuuden, kilpailukyvyn ja kannattavuuden kannalta? Hyötyykö yhteiskunta yritysten pyrkimyksistä kehittää henkilökuntansa osaamista? Vastauksia näihin kysymyksiin etsittäessä, pääpaino kohdistuu viime vuosina julkaistuihin tutkimuksiin yritysten tarjoamasta koulutuksesta sekä sen yksilöille, yrityksille sekä yhteiskunnalle tuottamasta taloudellisesta hyödystä. Yritysten tarjoaman koulutuksen vaikuttavuuden tutkimuksen suosio on kasvanut merkittävästi viimeisten kymmenen vuoden aikana. Osittain tähän ovat vaikuttaneet käytettävissä olevien aineistojen määrän ja laadun paraneminen sekä sofistikoidumpien tilastomenetelmien kehittyminen. Silti joutuu toteamaan, että nykyinen, teoreettiseen ja empiiriseen tutkimukseen pohjautuva tietämyksemme yritysten vuosittain henkilökuntaansa investoimien resurssien taloudellisesta merkityksestä on edelleen yllättävänkin vähäistä. Kokonaiskuvan hahmottamista hankaloittavat myös osittain ristiriitaiset tulokset. Nykyinen tietämyksemme antaa pohjan vain hyvin varovaisille politiikkasuosituksille. Tämä koskee sekä työnantajien tarjoaman koulutuksen jakautumisen että sen laajuuden vaikuttamiseen tähtääviä julkisen vallan interventioita. – henkilöstökoulutus ; tarjonta ; vaikuttavuus ; yritys
Keywords: J24; J31; M53; 330; Betriebliches Bildungsmanagement